2020
DOI: 10.1186/s13104-020-05398-3
|View full text |Cite
|
Sign up to set email alerts
|

Handwashing and disinfection precautions taken by U.S. adults to prevent coronavirus disease 2019, Spring 2020

Abstract: Objectives The objectives of this study were to assess self-reported hygiene precautions taken by U.S. adults during spring 2020 to prevent coronavirus disease 2019 (COVID-19) and to identify demographic characteristics associated with these hygiene precautions. Results We obtained data from Porter Novelli Public Services’s national survey, Spring ConsumerStyles, conducted March 19–April 9, 2020 among a nationally representative random sample of 6463 U.S. adults aged 18 years or older. We present data from th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…Socioeconomic status including education, income (higher), and sex (female) are negatively correlated with unhealthy behaviors [ 20 , 21 ]. In addition, the severity of comorbidities is closely related to the tendency toward healthy behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Socioeconomic status including education, income (higher), and sex (female) are negatively correlated with unhealthy behaviors [ 20 , 21 ]. In addition, the severity of comorbidities is closely related to the tendency toward healthy behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with more comorbidities tend to engage in more conservative behaviors for the sake of their health [ 22 ]. In United States adults (n = 6,463) from March to April 2020, hygiene-related behaviors such as handwashing and surface disinfection were more common among females and those older patients with higher income, higher education, and self-rated good health [ 21 ]. Except for self-rated health status, these findings are generally comparable to the observations made for the present CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, certain occupations are associated with higher likelihood of mortality from COVID-19 (Chen et al 2021). Third, studies that examined the uptake of health-related behaviours have also found that several social determinants of health are associated with the likelihood of handwashing (Alsan et al 2020;Brown et al 2020) and social distancing (Atchison et al 2021;Brankston et al 2021;Garnier et al 2021;Jay et al 2020;Weill et al 2020). Specifically, employment status has been identified as one of the important indicators of ability to take up protective behaviours (Brankston et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In Italy this percentage is also high, at 43 % (4). A study conducted in the United States showed that people with lower income and education had lower rates of handwashing and surface disinfection (5). In Brazil, 27%; in Ecuador, 24%; in Argentina, 20%; and in Peru, 18% do not wash their hands (4).…”
Section: Introductionmentioning
confidence: 99%